Infant processed food consumption and their interaction to breastfeeding and growth in children up to six months old - Renata Oliveira Neves; Luciano Santos Pinto Guimarães; Vera Lúcia Bosa; Leandro Meirelles Nunes; Clécio Homrich da Silva; Marcelo Zubaran Goldani; Juliana Rombaldi Bernardi (BMC, 2021)
Abstract Background Evidences suggest that early processed food (PF) consumption may cause harm to infant health. During the first 6 months of life, it is not known whether the timing and quantity of this food group can impact breastfeeding and growth. The aim of the study was to analyze the associations between time of introduction and quantity of infant PF consumption with duration of breastfeeding and infant growth at 6 months of age. Methods Data were longitudinally collected in six interviews, from birth to 6 months, in a sample of Brazilian newborns with adverse intrauterine environments. PF consumption was calculated by gravity score of processed foods (GSPF) in relation to feeding supply quality and time. For the analysis, the scores were divided into tertiles, making scores severities: Null, Mild, Moderate, and Severe. The interaction between GSPF and breastfeeding (exclusive and non-exclusive) and growth parameters (analyzed in Z-scores, by weight for height, weight for age, and body mass index for age) was tested. Results A total of 236 infants were included in the study. Greater GSPF were associated with better rates of breastfeeding practices and higher growth indicators scores in the sixth month of infants. These findings were confirmed after adjustment for family income, maternal age, pre-gestational body mass index, and growth z scores at birth. Conclusion The harms of eating PF in relation to breastfeeding and infant growth are more evident the greater and earlier they are consumed. Future studies should explore interventions to reduce and delay the consumption of these foods to prevent adverse health outcomes in later life.